Fertiliser on the rocks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Manure or compost are cheaper alternatives to commercial fertilisers, but you might be sitting on top of another one in your land, just waiting to be activated: inorganic phosphorous rock.Using the rock is in itself not new. In factories all around...